2019
DOI: 10.1186/s13756-019-0508-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of multidrug-resistant clinical Enterococcus faecalis isolates for antimicrobial resistance genes and virulence factors from the western region of Saudi Arabia

Abstract: Background: Enterococcus faecalis is a ubiquitous member of the gut microbiota and has emerged as a lifethreatening multidrug-resistant (MDR) nosocomial pathogen. The aim of this study was to survey the prevalence of multidrug-resistant and epidemiologically important strains of E. faecalis in the western region of Saudi Arabia using phenotypic and whole genome sequencing approaches. Methods: In total, 155 patients positive for E. faecalis infection were included in this study. The isolates were identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
33
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 49 publications
(52 reference statements)
14
33
2
4
Order By: Relevance
“…While resistance to penicillins and glycopeptides was absent, higher resistance rates were noted for ERY, TET, and LVX. The prevalence of ERY resistance (85.2%) was higher than in our previous study of puerperal infections in Bangladesh [11], and comparable to that reported for blood isolates in the US and Europe [31], and hospital isolates in the middle East [32]. The resistance rate to LVX (45.7%) was similar to that in our previous studies in Bangladesh [11] and the Middle East [32], but appears to be Figure 2.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…While resistance to penicillins and glycopeptides was absent, higher resistance rates were noted for ERY, TET, and LVX. The prevalence of ERY resistance (85.2%) was higher than in our previous study of puerperal infections in Bangladesh [11], and comparable to that reported for blood isolates in the US and Europe [31], and hospital isolates in the middle East [32]. The resistance rate to LVX (45.7%) was similar to that in our previous studies in Bangladesh [11] and the Middle East [32], but appears to be Figure 2.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of ERY resistance (85.2%) was higher than in our previous study of puerperal infections in Bangladesh [11], and comparable to that reported for blood isolates in the US and Europe [31], and hospital isolates in the middle East [32]. The resistance rate to LVX (45.7%) was similar to that in our previous studies in Bangladesh [11] and the Middle East [32], but appears to be Figure 2. Schematic representation of the genetic background of optrA in the E. faecalis strain SJ82 (uppermost) and the genetic organization or components similar to that of SJ82 in other strains reported previously [30] or available in GenBank database.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, the prevalence of Enterococcus faecalis in the unprocessed imported meat also highlights the complex pathogenic profile of the species inhabiting these meat products. E. faecalis is usually associated with nosocomial infections and has been reported as being one of the most challenging pathogens to treat due to its drug resistance [48,49].…”
Section: Microbial Community Profile In Meat Samplesmentioning
confidence: 99%
“…It not only links epithelial cells to virulent characteristics and resistant determinants via plasmid exchange and colonization but also attaches to the network of extracellular proteins (Wagner et al, 2018). Different studies have provided evidence that E. faecalis harbors the agg gene most (Guzman Prieto et al, 2016;Lins et al, 2019;Farman et al, 2019).…”
Section: Virulence Genes/factorsmentioning
confidence: 99%
“…Gelatinase hydrolyses collagen, bioactive peptides and gelatin. It as an extracellular Zn-metallo-endopeptidase which causes substantial damage to host tissue by splitting fibrin resulting in the dissemination of Enterococcus specifically E. faecalis (Farman et al, 2019) and involved in biofilm formation (Aladarose et al, 2019).…”
Section: Virulence Genes/factorsmentioning
confidence: 99%